Puisi Digital Generasi Z sebagai Praktik Multimodal di Media Sosial: Analisis Linguistik, Afektif, dan Interaksional - Nurul Humairah; I Nyoman Yasa (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
The rapid development of digital technology has significantly transformed literary practices, particularly in the way poetry is created and expressed by Generation Z. This study aims to examine the characteristics of digital poetry produced by Generation Z on social media using a multimodal approach. This research employs a qualitative descriptive method, with data collected from digital poems published on Instagram accounts @ruangtulisande_ and @almaneira. Data were obtained through digital observation and documentation techniques, and analyzed using multimodal analysis focusing on linguistic, visual-typographic, affective, and interactional aspects. The findings reveal that digital poetry demonstrates strong multimodal characteristics through the integration of text, visual presentation, emotional expression, and audience interaction. Linguistically, the poems reflect two dominant tendencies: existential self-reflection and intense interpersonal emotional expression. Visually, the poems adopt flexible and non-conventional structures that contribute to meaning-making. Affectively, they function as powerful media for emotional expression, while interactionally, social media platforms enable direct engagement between authors and audiences. In conclusion, digital poetry represents a transformation of contemporary literature, where meaning is constructed not only through language but also through multimodal elements and social interaction. This study highlights the relevance of multimodal analysis in understanding digital literary practices in the context of Generation Z culture